PEMANFAATAN GOOGLE SITES SEBAGAI MEDIA DALAM PEMBERIAN LAYANAN BK BAGI SISWA KELAS X DI SMK NEGERI 1 WIROSARI: PEMANFAATAN GOOGLE SITES SEBAGAI MEDIA DALAM PEMBERIAN LAYANAN BK BAGI SISWA SMK NEGERI 1 WIROSARI - Wijayanti, Inar Yulia (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
The purpose of this study was to determine the service process of BK teachers at SMK Negeri 1 Wirosari in providing Guidance and Counseling services through Google Sites. As well as knowing the experiences of students and BK teachers at SMK Negeri 1 Wirosari regarding Guidance and Counseling services carried out through Google Sites. The research approach uses descriptive qualitative with phenomenological methods. Research informants are BK teachers, principals, students, and students of class X. In this research instrument using a list of interviews and observation sheets. The use of the interviews and observations above is to dig up information and also make observations related to the use of Google Sites as a medium for counseling services at SMK Negeri 1 Wirosari. Data collection procedures are interviews, observation, and documentation. The data analysis technique uses an interactive analysis model. The result of the research is the process of classical BK teacher service using Google Sites. The way BK teachers deliver BK services is to provide information to students via whatsapp groups to open the Google Sites link to carry out BK services.